Evaluation of new generation systemic immune-inflammation markers to predict urine culture growth in urinary tract infection in children - Elgormus, Yusuf; Okuyan, Omer; Dumur, Seyma; Sayili, Ugurcan; Uzun, Hafize (Frontiers in Pediatrics, 2023)
Objective: Systemic inflammation has been implicated in urinary tract infection (UTI) development and progression. Accordingly, the aim of this study was to determine whether the white blood cell (WBC), the C-reactive protein (CRP), the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and the systemic immune-inflammation index (SII) are useful markers to predict of urine culture growth in children with UTI. Secondly, it was also to evaluate the prevalence of UTI pathogens, antibiotic resistance patterns, and empirical treatment options in children diagnosed with UTI by laboratory and clinical findings. Method: Study population comprised 413 cases (positive urine culture) and 318 cases (negative urine culture) with UTI. Results: There was no statistically significant difference in the medians of hemoglobin (HGB), hematocrit (HCT) and platelet (PLT) between the negative and positive culture groups. The median of monocytes, WBC, NLR, SII and CRP of the patients have positive urine culture was statistically significantly higher than the negative urine culture group. The AUC value was 0.747 (0.710-0.784) for CRP with a cut-off value of 3.2, the sensitivity is 56.4% and specificity is 98.4% in terms of UTI. The AUC value was 0.733 (0.697-0.769) for SII with a cut off value of 600, the sensitivity is 58.4% and the specificity is 83.0%. The AUC value was 0.732 (0.697-0.769) for NLR with a cut off value of 2, the sensitivity is 57.4% and the specificity is 81.1%. CRP (1.726; 95%CI: 1.536-1.939) and NLR (2.171; 95%CI: 1.856-2.540) had a higher OR. Conclusion: CRP and NLR may a useful independent diagnostic or complementary marker for disease in children diagnosed with UTI have positive urine culture. E. coli was the most common causative agent, the most used antibiotic is cephalosporin, high resistance to cefuroxime, trimethoprim-sulfamethoxazole (TMP-SMX), cefixime, ampicillin, and ceftriaxone was detected in all agents of UTIs in childhood in our center.